2020
DOI: 10.26434/chemrxiv.12605207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online in No Time: Design and Implementation of a Remote Learning First Quarter General Chemistry Laboratory and Second Quarter Organic Chemistry Laboratory

Abstract: The instruction of high enrollment general and organic chemistry laboratories at a large public 10 university always have curricular, administrative, and logistical challenges. Herein, we describe how we met these challenges in the transition to remote teaching during the COVID-19 pandemic. We discuss the reasoning behind our approach, the utilization of our existing web-based course content, the additions and alterations to our curriculum, replacement of experimental work with videos, the results of b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 115 A University of California–Irvine (Irvine, CA) general and organic chemistry team provided students with videos and sample data to analyze but then suddenly had to pivot the large end-of-semester organic exam to offer a choice of lower-stakes creative reflection assignments in response to national social upheaval. 86 These variations in curricular adjustments serve as reminders of the diversity of contexts in which education occurs.…”
Section: Curricular Adjustments For Erlmentioning
confidence: 99%
See 2 more Smart Citations
“… 115 A University of California–Irvine (Irvine, CA) general and organic chemistry team provided students with videos and sample data to analyze but then suddenly had to pivot the large end-of-semester organic exam to offer a choice of lower-stakes creative reflection assignments in response to national social upheaval. 86 These variations in curricular adjustments serve as reminders of the diversity of contexts in which education occurs.…”
Section: Curricular Adjustments For Erlmentioning
confidence: 99%
“…A convincing number of authors who assigned videos/worksheets/simulations to students remotely, distributed sample data, or required some form of data/procedural analysis reported that the students evidenced lower comprehension of data and procedures, greater discomfort, or poorerquality of interpretation than prior cohorts ( Box 1 ). 34 , 47 , 49 , 50 , 64 , 71 , 74 , 77 , 80 , 82 , 86 , 88 , 90 92 , 97 , 106 , 111 , 125 127 For example, physical chemistry students at Pennsylvania State University (University Park, PA) who watched videos and analyzed data were noticed by the instructor to copy out mistakes from the lab manual into their reports, despite the experimental video showing a different procedure. 82 Analytical chemistry students who watched videos and analyzed sample data for two laboratories and then did simulations and recorded simulated data for two more laboratories at Lander University (Greenwood, SC) appeared confused about the data, where it came from, what it meant, and how to analyze it, although the students did not appear as confused for the simulated data they recorded themselves.…”
Section: Student Outcomesmentioning
confidence: 99%
See 1 more Smart Citation